Gender-Informed Family Planning Perceptions and Decision-Making in Rural Chiapas, Mexico: A Mixed-Methods Study - Truong, Samantha; Villar de Onis, Jimena; Lindley, Alexa; Bazúa, Rodrigo; Reyes, Andrea; Montaño, Mariana; Marcotrigiano, Leanne; Molina, Rose L. (International Journal of Reproductive Medicine, 2020)
Compared to other Mexican states, Chiapas possessed the lowest rate of contraception use among women 15−49 years old (44.6%) in 2018. This convergent mixed-methods study assessed family planning use, perceptions, and decision-making processes among women and men in rural communities where Compañeros En Salud (CES) works in Chiapas, Mexico. We conducted surveys of reproductive-aged women and semi-structured interviews with reproductive-aged women, men, and physicians completing their social-service year in CES communities from 2016 to 2017. Of the 625 survey respondents, 368 (58.9%) reported using contraception. The most common methods were female sterilization (27.7%), bimonthly injection (10.9%), and the implant (10.9%). Interviews were completed with 27 women, 24 men, and 5 physicians and analyzed through an inductive approach. Common reasons for contraception use were preventing pregnancy, lack of resources for additional children, and birth spacing. Adverse effects, influence of male partners, and perceived lack of need emerged as reasons for non-use. Male partners often made the final decision about contraceptive use, while women often chose what method. Physicians reported adverse effects, misconceptions about methods, and lack of women’s autonomy as barriers to contraception use. Given misconceptions about contraception methods and the dominant role of men in contraception decision-making, our study illustrates the importance of effective counseling and equitable gender dynamics for family planning programming in rural Chiapas.